Plano de ação para promoção e prevenção do transtorno mental na UFRN - França, Maria da Conceição Silva de (2021)
This Intervention Project aims to build an Action Plan for promoting and preventing illness due to mental disorders, creating conditions for changes in this reality and providing subsidies for the formulation of the mental health policy at UFRN. It is justified by the absence of a mental health policy in the institution and by the contribution it will be able to make to reducing the incidence of mental and behavioral disorders striking its employees. The research and proposal approach is presented as a qualitative approach. The methodological path comprised two phases: a) diagnosis of the problem situation, through a bibliographic survey on illness due to Mental and Behavioral Disorders, leaves of absence, workloads, working conditions and analysing the institution's internal documents, such as the Management Report , PDI and Resolutions; b) interviews with representatives of the DAS - Divisões de Atenção à Saúde (Divisions of Attention to Health). Usually, it is the policy that defines the plan, programs and projects. Nonetheless, given the lack of formulation to the mental health policy and considering the need of forwarding cases of incidence of mental disorders that frequently occur in the institution, an Action Plan existance for the Mental Health then becomes an important element to treat people's health in a systematic and articulated way. It is believed that the Action Plan will contribute to adjustments to already existing actions and new proposals, bringing impacts regarding the care anticipation and changes in the scenario of illnesses and leaves of the institution's workers.